Health screening for children of primary education age (7 – 15 years) during the COVID-19 pandemic: The experience of Banyumas Regency - Wijayanti, Ayi; Suryo Bintoro, Bagas (BKM Public Health and Community Medicine, 2021)
Objective: Implementation of Health Screening for Elementary Education Age Children (Udiksar) is a routine program carried out by Puskesmas, including Banyumas Regency. The Puskesmas visit schools and carries out health screenings for children offline and simultaneously with the implementation of learning. Face-to-face learning has not run optimally due to the COVID-19 pandemic, so adjusting the Udiksar Health Screening is necessary without increasing the risk of COVID-19 transmission. Content: Udiksar's health screening is one of the indicators of Minimum Service Standards and regional performance indicators. Performance achievements for the Udiksar Health Screening in the first quarter of 2021 in Banyumas Regency decreased compared to 2020. In evaluating the activities in the first quarter of 2021, the main problem in implementing the Udiksar Health Screening activities were officers' difficulty reaching targets during the pandemic. The officer then consulted the evaluation results with the Central Java Provincial Health Office and referred to the implementation instructions issued by the Ministry of Health of the Republic of Indonesia. The plan to adjust Udiksar's Health Screening activities during this pandemic focuses on using Google Forms as a data collection tool for children's health information. This plan was presented in a Coordination Meeting with the Heads of Health Centers throughout Banyumas Regency in April 2021. The follow-up to be carried out was the Training of Officers in the use of Google Forms as an alternative solution to implementing the Udiksar Health Screening in April 2021. An evaluation in the 3rd quarter of 2021 showed 71.1% of successfully implemented new Google forms in urban areas. It is ineffective in rural areas and requires an alternative solution for implementing the Udiksar Health Screening. One practical recommendation is to provide a printed questionnaire collected within the regular collection of school assignments. Also, increasing cross-sectoral collaboration in implementing Udiksar screening activities can be done mainly through the collaboration of the School Health Business Development Team at the district and sub-district levels to obtain appropriate alternative solutions. Tujuan: Pelaksanaan Skrining Kesehatan pada Anak Usia Pendidikan Dasar (Udiksar) merupakan program rutin yang dilaksanakan oleh Puskesmas, termasuk di Kabupaten Banyumas. Puskesmas mengunjungi sekolah dan melaksanakan skrining kesehatan pada anak secara luring dan bersamaan dengan pelaksanaan pembelajaran. Pembelajaran tatap muka belum berjalan optimal akibat pandemi COVID-19, sehingga diperlukan penyesuaian Skrining Kesehatan Udiksar agar kegiatan tetap dapat dilaksanakan tanpa menimbulkan peningkatan risiko penularan COVID-19. Isi: Skrining kesehatan Udiksar merupakan salah satu indikator Standar Pelayanan Minimal dan indikator kinerja daerah. Pencapaian kinerja untuk Skrining Kesehatan Udiksar pada triwulan 1 2021 di Kabupaten Banyumas mengalami penurunan dibandingkan dengan tahun 2020. Pada evaluasi kegiatan triwulan 1 2021 didapatkan bahwa masalah utama pelaksanaan kegiatan Skrining Kesehatan Udiksar adalah kesulitan petugas untuk menjangkau sasaran di masa pandemi. Petugas kemudian mengkonsultasikan hasil evaluasi kepada Dinas Kesehatan Provinsi Jawa Tengah dan merujuk pada petunjuk pelaksanaan yang dikeluarkan oleh Kementerian Kesehatan Republik Indonesia. Rencana penyesuaian kegiatan Skrining Kesehatan Udiksar di masa pandemi ini mengerucut pada pemanfaatan Google Form sebagai alat pengumpulan data informasi kesehatan anak. Rencana ini dipaparkan dalam Rapat Koordinasi dengan Kepala Puskesmas se-Kabupaten Banyumas pada bulan April 2021. Tindak lanjut yang dilakukan adalah Pelatihan Petugas dalam pemanfaatan Google Form sebagai alternatif solusi pelaksanaan Skrining Kesehatan Udiksar pada periode April 2021. Evaluasi pada triwulan 3 2021 menunjukkan bahwa pemanfaatan Google Form baru berhasil diterapkan di kawasan urban dengan capaian sebesar 71,1%. Penggunaan Google Form tidak efektif di kawasan rural dan membutuhkan alternatif solusi pelaksanaan Skrining Kesehatan Udiksar. Salah satu rekomendasi praktis yang dapat dilakukan adalah dengan memberikan kuesioner cetak untuk pengumpulan data kesehatan yang dapat disisipkan bersamaan dengan pengambilan dan pengumpulan tugas sekolah berkala. Peningkatan kerjasama lintas sektor dalam pelaksanaan kegiatan skrining Udiksar dapat dilakukan terutama melalui kerjasama Tim Pembina Usaha Kesehatan Sekolah. Kerjasama ini dilakukan di level kabupaten maupun kecamatan, sehingga dapat diperoleh solusi alternatif yang tepat.